Is that a fish in your ear? : the amazing adventure of translation - Bellos, David (London : Penguin, 2012)
Without translation there would be no world news, not much of a reading list in any subject at college, and no repair manuals for cars or planes. This book ranges across the whole of human experience, from foreign films to philosophy, to show why translation is at the heart of what we do and who we are.
Originally published: Allen Lane, 2011.
Includes bibliographical references and index.
Keywords: Translating and interpreting; Translating and interpreting -- History